Oral Treatment with Plant-Derived Exosomes Restores Redox Balance in H2O2-Treated Mice - Rossella Di Raimo; Davide Mizzoni; Massimo Spada; Vincenza Dolo; Stefano Fais; Mariantonia Logozzi (MDPI AG, 2023)
Plant-derived exosomes (PDEs) are receiving much attention as a natural source of antioxidants. Previous research has shown that PDEs contain a series of bioactives and that their content varies depending on the fruit or vegetable source. It has also been shown that fruits and vegetables derived from organic agriculture produce more exosomes, are safer, free of toxic substances, and contain more bioactives. The aim of this study was to investigate the ability of orally administered mixes of PDE (Exocomplex®) to restore the physiological conditions of mice treated for two weeks with hydrogen peroxide (H2O2), compared with mice left untreated after the period of H2O2 administration and mice that received only water during the experimental period. The results showed that Exocomplex® had a high antioxidant capacity and contained a series of bioactives, including Catalase, Glutathione (GSH), Superoxide Dismutase (SOD), Ascorbic Acid, Melatonin, Phenolic compounds, and ATP. The oral administration of Exocomplex® to the H2O2-treated mice re-established redox balance with reduced serum levels of both reactive oxygen species (ROS) and malondialdehyde (MDA), but also a general recovery of the homeostatic condition at the organ level, supporting the future use of PDE for health care.